2020
DOI: 10.7554/elife.54875
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition stabilization is a widespread property of cortical networks

Abstract: Many cortical network models use recurrent coupling strong enough to require inhibition for stabilization. Yet it has been experimentally unclear whether inhibition-stabilized network (ISN) models describe cortical function well across areas and states. Here, we test several ISN predictions, including the counterintuitive (paradoxical) suppression of inhibitory firing in response to optogenetic inhibitory stimulation. We find clear evidence for ISN operation in mouse visual, somatosensory, and motor cortex. Si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
167
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(216 citation statements)
references
References 69 publications
30
167
1
Order By: Relevance
“…In this work, we have investigated responses in networks of spiking neurons at finite coupling. In this regime, which has recently been suggested to underlie cortical dynamics [ 24 , 25 , 41 , 42 ], we have shown that two types of nonlinearities emerge: response-onset and saturation. The network response transitions between these two nonlinearities as feedforward input increases; for intermediate inputs, the response matches that of the balanced-state model up to corrections of order .…”
Section: Discussionmentioning
confidence: 56%
“…In this work, we have investigated responses in networks of spiking neurons at finite coupling. In this regime, which has recently been suggested to underlie cortical dynamics [ 24 , 25 , 41 , 42 ], we have shown that two types of nonlinearities emerge: response-onset and saturation. The network response transitions between these two nonlinearities as feedforward input increases; for intermediate inputs, the response matches that of the balanced-state model up to corrections of order .…”
Section: Discussionmentioning
confidence: 56%
“…Pyr → VIP → SST → Pyr) that depends upon, and contributes to, network dynamics. Stabilized supralinear network (SSN) models have been proposed to account for a variety of contrast-dependent response properties in visual cortex ( Rubin et al, 2015 ; Ahmadian et al, 2013 ), including the transition from a high gain regime at low contrast to a feedback inhibition dominated low gain regime at high contrast ( Adesnik, 2017 ; Sanzeni et al, 2020 ), as well as cortical noise correlations ( Hennequin et al, 2018 ), surround suppression ( Liu et al, 2018 ), and effects of feature and spatial attention on neural activity ( Lindsay et al, 2020 ). In SSNs, high gain is achieved through supralinear single-neuron transfer functions (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…r vis : visual response period for analysis in C. Black and blue bars: duration of visual stimulus and optogenetic inhibitory stimulus, respectively. Vertical scale bars in panels vary, to more clearly illustrate relative suppression with optogenetic stimulation; quantification in panel C. The rightmost panel shows at the highest power a transient associated with ISN dynamics ( Sanzeni et al, 2020, Figure 5–Figure Supplement 2 ), which has ended by the time the visual response analysis period begins. V1, lateral, medial panels: N = 14, 6, 7 single units.…”
Section: Resultsmentioning
confidence: 99%